HUBUNGAN ANTARA KADAR TROMBOSIT PASIEN DENGAN KEBUTUHAN KASA STERIL PADA OPERASI SECTIO CAESAREA (SC) - Karsiyati karsiyati; Bondan Palestin; Surantono Surantono (Jurnal Kesehatan Karya Husada, 2014)
Background: Caesarean Section prevalences have been increasing globally annually. Hypovolemic shock may occur due to excessive bleeding that happened during procedure. Platelet is one of the three main haemostatic factors. Surgery sterile gauze may function as the local presser on bleeding intervention efforts. Perioperative nurses play an important role in the planning of both equipments and goods which would be required during surgery based on the procedures to be performed and the results of preoperative patient’s examination. The results of preoperative patient’s examination in the Installation of Surgery Panembahan Senopati Bantul District Hospital nowadays have not been used as a base for the planning of Caesarean Section sterile gauze demand during its procedures. The aim of This study was to determine the relationship between platelet levels of patients with sterile gauze demand on the SC procedures. Methods: This cross sectional study observed 43 patients who underwent Caesarean Section procedure with the normal Partial Thromboplastin Time (PTT) and activated Partial Thromboplastin Time (APTT) and not done under general anesthesia. Results: The average of patient’s platelet level was 256.000/uL and sterile gauze demand during SC procedure was 2,1507m2 equal to 27 pieces of gauze with the surface area of each piece was 0,08 m2. Product moment test showed patient’s platelet levels associated with the demands of sterile gauze in patients who underwent SC surgery as statistically (p: 0.000, correlation coefficient - 0.643, determination value 0,413 on the sygnificancy level 0.05). Conclusion: There is a negative and strong correlation between platelet levels of patients with sterile gauze demands during SC procedures